Screening forage and browse legumes germplasm to nutrient stresses: IGrowth rates of Sesbania as affected by aluminium and low phosphorus in soils and nutrient solutions - Mugwira, L.M.; Haque, I. (Informa UK Limited, 1993)
Sesbania have multifarious utilization, and in many instances growth rate is one of the most important criteria for the selection of suitable Sesbania. This paper reports results of a study on the growth rates of Sesbania on two acid soils both low in available P, but one with toxic levels of Al. Growth rate was assessed by measuring plant height at 21, 29, 35, 45, 52, and 60 days on a clay loam (chencha soil). Growth was also evaluated in nutrient solutions containing 0, 3, and 6 PPm Al in combination with 155 and 6200 PPm On the Soddo soil, the Sesbania varied in their growth rates, but responded similarly to liming the soil from PH 4.8 to 5.6 throughout the growing period. The accessions showed similar response to P during early growth, but varied sharply during late growth 35 to 60 days without Lime was progressively move effective with P applied. The growth patterns fell into four categories based on responses to P applied to the Soddo soil. On the Chencha soil which had 77 percent Al saturation, the Sesbania differentially responded to liming the soil from PH 4.1 to 5.9 and to applied P at each growth interval. Accessions which had the best plant height on the Chencha soil were generally tolerant to Al. Variability in the growth rates of accessions from different countries suggested potential for screening Sesbania for differential tolerance to soil acidity and low P in relation to source of origin.